Pengaruh Kepercayaan, Keamanan dan Kemudahan terhadap Keputusan Pembelian pada E-commerce Shopee di Kota Batam - Tiurmaida, Yohana Abigail; Suhardi, Suhardi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of trust, security, and convenience on purchasing decisions on the Shopee e-commerce platform in Batam City. The main issue addressed in this study is the inconsistency in consumer behavior, where concerns about product quality, user data security, and platform complexity continue to arise despite Shopee’s popularity. The objective of this study is to determine whether these three variables significantly impact consumers' purchasing decisions both individually and collectively. This research employed a quantitative approach using purposive sampling, with data collected through questionnaires from 100 Shopee users. Data were analyzed using SPSS version 30, applying multiple linear regression analysis, classical assumption testing, and hypothesis testing. The findings show that trust, security, and convenience each have a positive and significant effect on purchasing decisions, with t-values of 2.769 (p = 0.007), 2.684 (p = 0.009), and 3.138 (p = 0.002) respectively. Simultaneously, the F-test indicates a significant effect (F = 18.950, p < 0.001), and the adjusted R² value of 0.352 suggests that 35.2% of the purchasing decision can be explained by the three variables. The study implies that enhancing these aspects is crucial for improving consumer loyalty and conversion on e-commerce platforms like Shopee.